“O Guerreiro de Alagoas” and folkmarketing: relationships between folklore, cultural identity and place branding (Revista Internacional de Folkcomunicação, 2018)
ABSTRACT Alagoas has a vast culture being considered the Brazilian state that holds one of the greatest diversities of folkledos and popular manifestations. “O Guerreiro de Alagoas”, a manifestation born in Maceió, is the party with the highest representation in the state, but it needs to strengthen its visibility not only as a potential tourist attraction, but also as a vector of local cultural identity. Folkmarketing is imperative to change the current scenario, as well as place branding, leading to the construction of a competitive image of the Alagoan capital. It is urgent to show that there are more than beautiful beaches; there are also strong cultural traditions. Through an accurate analysis of folklore combined with bibliographical research, the study ratifies the importance of the manifestation as an element of cultural identity of the Alagoan people, besides suggesting practical actions capable of promoting in the local population and visitors the value of this intangible cultural heritage. KEY-WORDS “Guerreiro de Alagoas”; Folkmarketing; Cultural identity; Patrimony; Place branding.